Analytical fragility curves for displacement-based scour assessment of masonry arch bridges. (December 2022) - George, Jofin; Menon, Arun
Abstract: The vulnerability of masonry arch bridges to scouring is primarily attributed to their shallow foundations. There is a constant need to assess the structural safety and identify those masonry arch bridge geometries susceptible to scouring. The immediate structural effect of scouring is the mobilisation of the bridge foundation resulting in the formation of a collapse mechanism involving the bridge superstructure. There is a critical gap in the literature in the availability of simple quantitative assessment procedures applicable to a population of masonry arch bridges susceptible to scouring. In this context, a generalised assessment procedure, primarily dependent on the geometry, is presented, which identifies bridge geometries susceptible to scouring through the quantification of available safety margin. The possible in-plane foundation movements and associated collapse mechanisms are identified as a function of bridge typology and the nature of scouring. Displacement-based analysis procedures are formulated the first principles for each identified in-plane collapse mechanism, replicating the observed collapse behaviour of masonry arch bridges. Fragility curves are then presented for each collapse mechanism with performance levels prescribed based on deformation demand, giving the exceedance probability for a developed foundation movement.